Images in Mobile Communication New Content, New Uses, New Perspectives - Martin, Corinne; Pape, Thilo; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2012)
This volume provides an original perspective on mobile communication, focusing on the emerging deployment of images in mobile phone usage: photography, video, mobile television, mobile internet, etc. Deeply embedded in our audiovisual culture, images possess the undeniable power to reshape the future of the mobile phone as an individual mass medium. In this collection, European researchers in media and communication studies, sociology, anthropology and political science present empirical and conceptual work on a wide range of issues, including cultural change, new forms of sociability on individual and societal levels, tactics and strategies of users and producers, and finally, representations and imaginaries of the mobile phone in other established media. This book is written for researchers and students of sociology, communication studies and cultural studies as well as for practitioners of interactive media and online communication.
Keywords: Social sciences; Social Sciences; Communication Studies